Penerapan Model Pembelajaran Tutor Sebaya untuk Meningkatkan Hasil Belajar IPA Tema Sistem Pencernaan Manusia Pada Siswa Kelas V SD Negeri 57 Kota Ternate - Harina Sangadji (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is Classroom Action Research (CAR). The research was conducted at SD Negeri 57 Ternate City. The research subjects were Class V students, totaling 39 students. Where there are 19 female students and 20 male students. The research was conducted from July - September 2022. Data collection was carried out using qualitative (observation) and quantitative (evaluation) analysis. Based on the results of research and discussion obtained the value of the pre-cycle is 56.28. This shows that student learning outcomes before using integrated learning can be categorized as low or lacking, because they are below the average KKM value previously set, which is 70. With planning and actions designed in such a way in cycle 1 the learning outcomes obtained are not good enough, namely has not exceeded the KKM value limit with an average value of 65.25, the learning outcomes continue to be improved by correcting the deficiencies that exist when the action is carried out through reflection. The results obtained in cycle 2 are quite increased with an average value of 80.40. This learning result is an average grade that is quite satisfactory because it has exceeded the KKM value limit previously set. So it can be concluded that the application of peer tutoring is fun learning and helps students understand science learning in elementary schools more easily so that they achieve satisfactory grades.